2017
DOI: 10.2460/javma.251.4.443
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic ovariectomy and laparoscopic-assisted ovariohysterectomy in dogs: 278 cases (2003–2013)

Abstract: OBJECTIVE To compare outcomes for laparoscopic ovariectomy (LapOVE) and laparoscopic-assisted ovariohysterectomy (LapOVH) in dogs. DESIGN Retrospective case series. ANIMALS 278 female dogs. PROCEDURES Medical records of female dogs that underwent laparoscopic sterilization between 2003 and 2013 were reviewed. History, signalment, results of physical examination, results of preoperative diagnostic testing, details of the surgical procedure, durations of anesthesia and surgery, intraoperative and immediate posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Intraoperative complication rates in 278 laparoscopic spay procedures were reviewed a recent study. Ten (4%) of the procedures had intraoperative complications . Intraoperative complications in 1.6% of cases were found in another large study of 618 laparoscopic ovariectomies in dogs .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Intraoperative complication rates in 278 laparoscopic spay procedures were reviewed a recent study. Ten (4%) of the procedures had intraoperative complications . Intraoperative complications in 1.6% of cases were found in another large study of 618 laparoscopic ovariectomies in dogs .…”
Section: Discussionmentioning
confidence: 94%
“…Ten (4%) of the procedures had intraoperative complications. 22 Intraoperative complications in 1.6% of cases were found in another large study of 618 laparoscopic ovariectomies in dogs. 23 Neither of the articles describing these studies reported laparoscopic entry-related complications or discussed minor complications such as gas leaks or repeated entry attempts.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because of the close similarity between laparoscopic ovotesticular gonadectomy and laparoscopic ovariectomy or cryptorchidectomy, the authors expect patients to benefit from the same described advantages, including increased visualization (Mayhew, 2009), decreased intraoperative bleeding (Charlesworth & Sanchez, 2019), shorter recovery time, increased post‐operative activity level (Culp, Mayhew, & Brown, 2009), decreased post‐operative pain (Devitt et al., 2005; Hancock et al., 2005) and decreased overall and wound healing complications (Charlesworth & Sanchez, 2019). When abdominal exploration would reveal uterine abnormalities requiring its removal, the procedure can easily be converted to a laparoscopy‐assisted gonadohysterectomy, similar to laparoscopy‐assisted ovariohysterectomy and still offer minimally invasive benefits to the patient (Corriveau, Giuffrida, Mayhew, & Runge, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the strength of this evidence was questioned by a systematic review of peer‐reviewed original English journal articles, recent results have confirmed this causal relationship . Prevalence rates of AUI up to 20% have been reported; however, they vary tremendously among studies, most likely reflecting different demographic compositions . Breed, size, or bodyweight of the dog; obesity or body condition score (BCS); tail docking; urethra length; age of the dog; and the time of spaying in relation to the onset of puberty are considered potential risk factors of AUI.…”
Section: Introductionmentioning
confidence: 99%